Movies: the Audience Favorites - Alexander, Fedorov (Academic Publishing House Researcher, 2018)
Modern screen art over its success to the use of folklore, myth, synthesis of the natural and supernatural, and a consistent orientation toward the most popular plot schemes. Their metaphorical appeal is not to the rational but to the emotional, through identification with the magic power of heroes and standardization of ideas, situations, characters and so on in compensation for dreams not realized in life, there are illusions – happy endings. In movies, TV shows, and music videos' rhythmic organization, viewers' feelings are influenced as much by the order of changing shots as by the content of productions. On the basis of the foregoing, it can be concluded that the media texts of popular culture obliged to a variety of factors for its success. These include: reliance on folklore and mythological sources, constancy metaphors, focus on consistent implementation of the most persistent plot schemes, the synthesis of the natural and the supernatural, the appeal not to rational and emotional, through the identification of (imaginary transformation in of active characters merge with the atmosphere, the aura of works), “magic power” of heroes, standardization (replication, unification, adaptation) ideas, situations, characters, etc., mosaic, seriality, the compensation (of the cherished illusion, but not come true desires), the happy ending, the use of such rhythmic organization movies, TV shows, clips, where the feeling of the audience with the content of the frame affects the order of their shift; intuitive guessing subconscious audience interests, etc.